Meningkatkan Motivasi dan Hasil Belajar IPS Siswa Kelas VI SD melalui Model Group Investigation - Astuti, Budi (Mimbar Sekolah Dasar, 2017)
The aim of this research is to increasing the students’ motivation and study result IPS in material kenampkan alam dan kenampakan alam negara-negara tetangga fourth grade of elementary school. This research used classroom action research method. The action was doing 2 times on two cycles. Every cycle consist at 3 meeting in class. This cycle consist at 4 steps such as planning, action, monitoring and reflection. The data were collecting in four months, starting from September until December 2016. The subject of this research is seventeen students at fourth grade of SDN 2 Tutup Blora.  This class consist at 4 male and 13 female students. The conclusion of this research reported that Group Investigation teaching model could increased the students’ motivation and study result in fourth grade of SDN 2 Tutup Blora.